2017
DOI: 10.1371/journal.pone.0179423
|View full text |Cite
|
Sign up to set email alerts
|

High tolerance to temperature and salinity change should enable scleractinian coral Platygyra acuta from marginal environments to persist under future climate change

Abstract: With projected changes in the marine environment under global climate change, the effects of single stressors on corals have been relatively well studied. However, more focus should be placed on the interactive effects of multiple stressors if their impacts upon corals are to be assessed more realistically. Elevation of sea surface temperature is projected under global climate change, and future increases in precipitation extremes related to the monsoon are also expected. Thus, the lowering of salinity could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Such information is extremely important to understand how coral larvae respond and cope with the highly dynamic natural field conditions. Interestingly, previous study on the larvae of another coral species in Hong Kong, Platygyra acuta, has shown high tolerance to elevated temperatures (+3 °C and +5 °C above ambient) that did not cause any negative effects on larval settlement success and post-settlement survival for up to 56 days of prolonged exposure (Chui and Ang, 2017). Further research is necessary to compare their molecular responses which might reveal the possible underlying mechanisms contributing to the difference in thermal tolerance among species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such information is extremely important to understand how coral larvae respond and cope with the highly dynamic natural field conditions. Interestingly, previous study on the larvae of another coral species in Hong Kong, Platygyra acuta, has shown high tolerance to elevated temperatures (+3 °C and +5 °C above ambient) that did not cause any negative effects on larval settlement success and post-settlement survival for up to 56 days of prolonged exposure (Chui and Ang, 2017). Further research is necessary to compare their molecular responses which might reveal the possible underlying mechanisms contributing to the difference in thermal tolerance among species.…”
Section: Discussionmentioning
confidence: 99%
“…While the effects of temperature stress on early stages of coral have been relatively well explored, there has been comparatively little focus on examining the salinity effect (Mayfield and Gates, 2007;Berkelmans et al, 2012). Reduction in salinity has been shown to reduce fertilization success (Richmond, 1993;Humphrey et al, 2008;Chui and Ang, 2015;Hedouin et al, 2015), increase developmental abnormality (Humphrey et al, 2008;Chui and Ang, 2015;Hedouin et al, 2015;Chui et al, 2016), and increase pre-and post-settlement mortality (Vermeij et al, 2006;Scott et al, 2013;Chui and Ang, 2017). Corals are known as osmoconformers (Hoegh-Guldberg and Smith, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation